Pengaruh Praktik Kerja Industri, Bimbingan Karir, Motivasi Memasuki Dunia Kerja dan Soft Skill terhadap Kesiapan Kerja - Pratiwi, Nova; Lestari, Neta Dian; Januardi, Januardi (Universitas Nusantara PGRI Kediri, 2024)
Examining the influence of industrial work practice, career counseling, encouragement to enter the world of work, and soft skills on work preparation is the purpose of this study. The research population was all XII grade students of SMK N 5 Palembang totaling 400 people, a research sample of 129 was determined through the G*power program, data collection techniques using questionnaires and multiple regression (ARM) with the backward method assisted by SPSS 26 for data analysis. The test results for the R coefficient of multiple regression models provide a test statistical value of F = 27.148, and a p-value (Sig.) <0.001. The regression model test results show that the initial model with 4 independent variables is not significant in explaining variations in work readiness, then the backward ARM suggests an improved model by discarding variables (X3) and (X4), so that a standardized regression equation Y = 2.186 + 0.299X1 + 0.455X2 is obtained, and the value of R2 = 0.457. This can be interpreted that with a contribution of 45.7% industrial work practices and career counseling have a positive and important impact on work readiness. The research results indicate that career counseling activities and industrial work practices are very important in helping students prepare for the world of work competition after they graduate.